Application of Appropriate Technology for Processing Worm Raw Materials and Standardization of Their Content: Penerapan Teknologi Tepat Guna Pengolahan Bahan Baku Cacing dan Standardisasi Kandungannya - Utami, Wahyu; Fauzi, Ahmad; Vitasari, Denny; Wahyuni, Arifah Sri (Prosiding University Research Colloquium, 2023)
The University of Muhammadiyah Surakarta community service team has carried out a series of service activities through the Community Service Program for the Application of Appropriate Technology (P2TTG) in collaboration with CV Berkah Alam as a service partner. This service aims to transfer technology in the processing of worm raw materials and standardization of their content to improve product quality. This service program will be carried out starting December 2021 for six months. The team carried out a series of studies related to earthworm processing and standardization of protein content then developed and applied it to improve production efficiency and product quality. Research and development carried out includes optimization of protein extraction from worm capsule samples, related to the optimum time and temperature to obtain the highest protein content. Furthermore, validate the protein analysis method in the worm capsule sample to ensure that the analysis method used is valid, accurate and presice to measure the protein content in the sample. Furthermore, training on efficient processing of worm raw materials to obtain maximum protein content and standardization of the production process.